Pre-synaptic DC bias controls the plasticity and dynamics of three-terminal neuromorphic electrolyte-gated organic transistors - Federico Rondelli; Anna De Salvo; Gioacchino Calandra Sebastianella; Mauro Murgia; Luciano Fadiga; Fabio Biscarini; Michele Di Lauro (Neuromorphic Computing and Engineering, 2023)
The role of pre-synaptic DC bias is investigated in three-terminal organic neuromorphic architectures based on electrolyte-gated organic transistors—EGOTs. By means of pre-synaptic offset it is possible to finely control the number of discrete conductance states in short-term plasticity experiments, to obtain, at will, both depressive and facilitating response in the same neuromorphic device and to set the ratio between two subsequent pulses in paired-pulse experiments. The charge dynamics leading to these important features are discussed in relationship with macroscopic device figures of merit such as conductivity and transconductance, establishing a novel key enabling parameter in devising the operation of neuromorphic organic electronics.